NOS knockout or inhibition but not disrupting PSD-95-NOS interaction protect against ischemic brain damage. Issue 9 (September 2016) - Kleinschnitz, Christoph; Mencl, Stine; Kleikers, Pamela WM; Schuhmann, Michael K; G López, Manuela; Casas, Ana I; Sürün, Bilge; Reif, Andreas; Schmidt, Harald HHW
Promising results have been reported in preclinical stroke target validation for pharmacological principles that disrupt the N-methyl-D-aspartate receptor–post-synaptic density protein-95–neuronal nitric oxide synthase complex. However, post-synaptic density protein-95 is also coupled to potentially neuroprotective mechanisms. As post-synaptic density protein-95 inhibitors may interfere with potentially neuroprotective mechanisms and sufficient validation has often been an issue in translating basic stroke research, we wanted to close that gap by comparing post-synaptic density protein-95 inhibitors with NOS1 −/− mice and a NOS inhibitor. We confirm the deleterious role of NOS1 in stroke both in vivo and in vitro, but find three pharmacological post-synaptic density protein-95 inhibitors to be therapeutically ineffective.